Produção e Aplicação de Biossurfactante Vegetal na Estabilização de Nanopartículas de Prta como Agentes Antibacterianos. - Ferreira, Hozana de Souza (2024)
Biosurfactants have been widely explored for their diverse bioactive properties, including the potential to stabilize silver nanoparticles, which can be an alternative to chemical surfactants that are toxic to humans and the environment. Therefore, the objective of this study was to extract surfactant molecules from tangerine (Citrus reticulata) residues and evaluate their surfactant and emulsifying properties, testing their potential as a stabilizing agent for silver nanoparticles (AgNPs) and as an antimicrobial agent. For this, three extraction methods were tested, so that the acid-base method was chosen because it enhanced the obtaining of an extract capable of reducing the surface tension of water from 72 to 30 mN/m, with a CMC of 0.7 % and yield of 1.0 g/Kg. Its stability was confirmed after carrying out tests under extreme pH and temperature conditions. The extract was anionic in nature and was not toxic to vegetable seeds and the microcrustacean Artemia salina. The silver nanoparticles synthesized with the extract were identified and characterized through analyzes with ultraviolet visible spectroscopy (UV/Vis), scanning electron microscopy (SEM) and zeta potential. UV/Vis showed a maximum absorption peak at 400-450 nm, characteristic of nanoparticles. SEM microscopy identified the formation of nanoparticles with predominantly spherical morphology featuring sizes in the range of 384-568 nm. The zeta potential was - 86.30 mV, showing that the presence of the biosurfactant promoted stability of the silver nanoparticles. The antimicrobial activity of AgNPs synthesized with plant biosurfactant was evaluated against pathogenic microorganisms (Echerichia coli and Staphylococcus aureus), which proved to be sensitive. Therefore, the biosurfactant extracted from tangerine peel is a promising stabilizer of silver nanoparticles, in addition to having potential as an antimicrobial agent.